A multiparametric-multilayer comparison of the preparation phase of two geophysical events in the Tonga-Kermadec subduction zone: the 2019 M7.2 Kermadec earthquake and 2022 Hunga Ha’apai eruption - D’Arcangelo, Serena; Regi, Mauro; De Santis, Angelo; Perrone, Loredana; Cianchini, Gianfranco; Soldani, Maurizio; Piscini, Alessandro; Fidani, Cristiano; Sabbagh, Dario; Lepidi, Stefania; Di Mauro, Domenico (Frontiers in Earth Science, 2023)
The Tonga-Kermadec subduction zone represents one of the most active areas from both seismic and volcanic points of view. Recently, two planetary-scale geophysical events took place there: the 2019 M7.2 earthquake (EQ) with the epicentre in Kermadec Islands (New Zealand) and the astonishing 2022 eruption of Hunga Tonga-Hunga Ha'apai (HTHH) volcano. Based on the Lithosphere-Atmosphere-Ionosphere Coupling (LAIC) models, we analysed the three geolayers with a multi-parametric approach to detect any effect on the occasion of the two events, through a comparison aimed at identifying the physics processes that interested phenomena of different nature but in the same tectonic context. For the lithosphere, we conducted a seismic analysis of the sequence culminating with the main shock in Kermadec Islands and the sequence of EQs preceding the HTHH volcanic eruption, in both cases considering the magnitude attributed to the released energy in the lithosphere within the respective Dobrovolsky area. Moving to the above atmosphere, the attention was focused on the parametersgases, temperature, pressurepossibly influenced by the preparation or the occurrence of the events. Finally, the ionosphere was examined by means of ground and satellite observations, including also magnetic and electric field, finding some interesting anomalous signals in both case studies, in a wide range of temporal and spatial scales. The joint study of the effects seen before, during and after the two events enabled us to clarify the LAIC in this complex context. The observed similarities in the effects of the two geophysical events can be explained by their slightly different manifestations of releasing substantial energy resulting from a shared geodynamic origin. This origin arises from the thermodynamic interplay between a rigid lithosphere and a softer asthenosphere within the Kermadec-Tonga subduction zone, which forms the underlying tectonic context.